The forensic confirmation bias: Problems, perspectives, and proposed solutions - Kassin, Saul M.; Dror, Itiel E.; Kukucka, Jeff (Journal of applied research in memory and cognition, 2013)
As illustrated by the mistaken, high-profile fingerprint identification of Brandon Mayfield in the Madrid Bomber case, and consistent with a recent critique by the National Academy of Sciences (2009), it is clear that the forensic sciences are subject to contextual bias and fraught with error. In this article, we describe classic psychological research on primacy, expectancy effects, and observer effects, all of which indicate that context can taint people's perceptions, judgments, and behaviors. Then we describe recent studies indicating that confessions and other types of information can set into motion forensic confirmation biases that corrupt lay witness perceptions and memories as well as the judgments of experts in various domains of forensic science. Finally, we propose best practices that would reduce bias in the forensic laboratory as well as its influence in the courts. Highlights ► The forensic sciences are subject to contextual bias and fraught with error. ► Basic psychology shows that context can taint perception, judgment, and behavior. ► Newer studies find that biasing information likewise impacts forensic scientists. ► Recommendations are given to reduce the effect of bias in forensic labs and courts.